Vrejlev Klosterkirkes middelalderlige bygningshistorie - Lindholt, Pia Katrine; Larsen, Morten (Kuml, 2021)
The nunnery church at Vrejlev buildings history By the end of the Middle Ages, the Premonstratensian nunnery at Vrejlev was characterised by a large and voluminous church. However, the Late Medieval building incorporated several features derived from a large Romanesque church established already in the mid-12th century. This article deals with the buildings-archaeological evidence, which provides a detailed overview of the site’s complicated buildings history and thereby sheds light on an important ecclesiastical centre in Medieval Vendsyssel (figs. 1-6). The church was originally constructed as a large three-aisled basilica, comparable with the existing church at Skarp Salling in Himmerland. The use of large granite ashlars, displaying a refined architecture, signifies a trend and knowhow that could have originated in the larger workshops of Viborg cathedral. The construction of the church at Vrejlev probably took place in the second half of the 12th century (figs. 7-13). In the 13th century, the church was damaged by fire, prompting repair works on the large building. During the 14th century there is no clear evidence for building activity on the site, but this increased markedly during the 15th century. A tower was erected in the 1420s, and during the final decades of the 15th century the church was completely rebuilt with bricks and converted into a large, two-aisled vaulted church displaying the architectural trends of the decades prior to the Reformation (figs. 14-18).